(untitled) (European Journal of Pure and Applied Mathematics, 2021)
This is a compilation of definite integrals involving the Lerch, Polylogarithm, Hurwitz functions and fundamental constants. Connections to previous work is compared and discussed. This collection of definite integrals is new in current literature.